REVITALISING THE MEANING OF TARTĪL “A Semantic-Linguistic Study of QS. al-Muzzammil (73): 4 in the Context of Contemporary Qur'an Recitation” - Rohma, Dika Purnama Aulia; Al Kausar, Abdurrahman; Mubarokah, Nur Lailatul; Febrianti, Dona (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2025)
One of the main rules in the practice of recitation according to the scholars is to read the Qur'an in a tartīl manner. However, the tendency of reciting the Qur'an in the contemporary era that focuses more on the aesthetic aspects of sound and ignores the dimensions of understanding, order, and adab in reading becomes the main crisis in reciting the Qur'an. Therefore, this paper contributes to revitalizing the concept of tartīl in contemporary recitation practices to bring it back in line with the values of the Qur'an. This study utilises library research with a thematic interpretation approach and semantic-linguistic analysis of QS. al-Muzzammil [73]: 4. This study analyzes the meaning of tartīl in QS. al-Muzzammil [73]: 4 according to two prominent mufasirs, namely al-Ṭabarī and al-Nasafī, and compares it with the views of classical qirā'āt scholars. The results of the study indicate that tartīl, according to the majority of mufassir, encompasses aspects of clarity of recitation, calmness, orderliness of verses, and depth of meaning. Additionally, according to scholars of qira’at tartīl, it involves reciting the Qur’an slowly, clearly, and in a structured manner, with full contemplation. Concrete steps for revitalizing tartīl include strengthening Quranic education based on tartīl in formal and non-formal institutions, training Quranic recitation teachers who integrate aspects of tajwīd and tadabbur, developing educational digital media that promote the values of tartīl, the establishment of standards and certification for tartīl recitation, and the cultivation of tadabbur within Muslim communities through meaningful halaqah and tilawah gatherings. The revitalization of tartīl in the contemporary era must be based on a holistic understanding to maintain a balance between the speed of recitation and the quality of pronunciation and the contemplation of meaning.